Biomineralization 2018
DOI: 10.1007/978-981-13-1002-7_37
|View full text |Cite
|
Sign up to set email alerts
|

The Marsh’s Membrane: A Key-Role for a Forgotten Structure

Abstract: Recent imaging methods applied to the growing edge of the Pinctada margaritifera shell allow for a better appreciation of ancient structural data. Growth of the Pinctada shell (both lateral extension and thickness increase) is a coordinated mechanism involving a series of clearly identified steps in contrast to the prevailing concept of a direct "self-assembly" process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…With respect to size, shape and position, these circular units are similar to the structures previously described on the periostracum of the Pinctada margaritifera shell, the Polynesian pearl oyster ( Cuif and Dauphin, 2018 ). This species also produces an outer shell layer built by calcitic prisms although, compared with the Pinna shells, the respective importance of the outer and inner shell layers are in reverse proportions.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…With respect to size, shape and position, these circular units are similar to the structures previously described on the periostracum of the Pinctada margaritifera shell, the Polynesian pearl oyster ( Cuif and Dauphin, 2018 ). This species also produces an outer shell layer built by calcitic prisms although, compared with the Pinna shells, the respective importance of the outer and inner shell layers are in reverse proportions.…”
Section: Discussionsupporting
confidence: 73%
“…It is also worth to note that the mineralizing surface of the prisms is covered by the Marsh's membrane. This continuous translucent organic film is so closely attached to the shell surface that the ridges and grooves remain visible, although attenuated ( Figure 7 h) ( Cuif and Dauphin, 2018 ). Existence of corresponding substructures in this membrane is emphasized by epipolarization ( Figure 7 i).…”
Section: Resultsmentioning
confidence: 99%
“…This point is important because, after being incorporated into the shell growing edge, these calcite units are acting as substrates for crystallization of the prisms. The amorphous calcium carbonate simultaneously secreted by the mantle cells will crystallize by following the crystalline orientation of the underlying disks [18]. Note must be made that from this point, growth of the prisms is simultaneous [16,19], whereas periostracal disks individually grow.…”
Section: Periostracum In the Pinctada Shells: Its Role In Shell Forma...mentioning
confidence: 99%
“…In the development of the shell growing edge, it has been shown that periostracum is acting only as a conveyor belt moving the calcite disks from the deeper part of the outer mantle grove up to the shell border [16]. Crystalline orientation of the calcite disks is given by the initial organic centers deposited onto the internal surface of the periostracum [18]. In contrast, the organic layer secreted by the pearl sac and progressively covering the nucleus (Figure 7A-C) has a leading role regarding crystalline orientation of the tiny mineral particles it is bearing.…”
Section: Origin Of Crystalline Orientation In Shell Prisms Compared W...mentioning
confidence: 99%
“…From a biomineralization viewpoint, these calcareous discs are remarkable because in spite of freely crystallizing (no contact between them) and a roundshaped morphology they exhibit a single-crystal behaviour (Figure S1F). With respect to their future function as mineralizing substrate for growth of the calcite prisms, this crystallographic property is an essential pattern (Cuif & Dauphin, 2018c).…”
Section: Is the Early Organic Secretion Of The Graft Comparable To Sh...mentioning
confidence: 99%